Multi-wavelength study of neutron stars in the Magellanic Clouds - Titus, Johanna (Department of Astronomy, 2023)
Massive stars are essential drivers of galaxy evolution, as well as the synthesis of heavier elements, enriching the interstellar and intergalactic medium with metals through every cycle of star formation. Thus to understand the evolving universe, it is essential to quantify the formation and evolution of massive stars in different environments. Most massive stars are born in binaries, as such their evolution are significantly affected by episodes of mass transfer. In this thesis I explore neutron stars, one of the endpoints of massive stars' evolution, in a bid to further understand the effects of binarity on evolution. To start, I conduct an optical spectroscopic and timing study of candidate X-ray binaries in the Large Magellanic Cloud (LMC), resulting in a 50% increase in the confirmed population of accreting neutron stars in the LMC. Following this study, I carry out a targeted radio pulsar search in the Small Magellanic Cloud (SMC), leading to the discovery of new pulsars, corresponding to a population size increase of 40%. The new radio pulsars allow for further characterisation of the SMC pulsar population. To relate these observational incarnations of neutron stars (i.e. radio pulsars and accreting X-ray pulsars), I utilise a binary population synthesis code that enables the prediction of pulsars in the SMC under the assumption that all pulsars are products of massive binary evolution. The simulations successfully reproduce the observed radio pulsar population of the SMC. Ultimately, pairing observational results with simulations can establish practical guidelines for future surveys, and provide a basis for using different observed populations of neutron stars to constrain binary interactions and evolution.